Study of the Fatigue of Chemistry Teachers in the Last Hours of Teaching the School Program in the Classroom - Drougas, Vasileios; Drouga, Ifigeneia V. (International Journal of Education Research and Development, 2024)
This paper examines the fatigue of the Chemistry Teachers who teach the Science of Chemistry in the first grade of high school in Greece. Twenty secondary school teachers aged 40-50 who teach first grade during the last two hours of the program participated in the study. In this research, significant problems were found in teaching and teacher fatigue and serious conclusions can be recorded about teaching the last two hours in the school. Also searched how the students participated in the previous hours of the weekly program in the last two days of the week. Teachers feel tired in the previous hours and it seems that it is difficult to teach chemistry science. They do not have the ability and time to participate in any laboratory experiments with the students. Founded that students are very tired in the last two hours. It turns out that they would like more hours of Chemistry in the weekly schedule for the first grade and think that it is difficult for the students to pay attention to the Chemistry teaching. Also in the last hours, many students leave the school. The research recognizes that it is much better to have chemistry lessons in the first hours of the school schedule rather than the last hours, also to have more time in the first grade for the chemistry lesson so that the teachers can use laboratory experiments with the students and to have more time for teaching.